Ultralong‐Life Quasi‐Solid‐State Li‐O2 Batteries Enabled by Coupling Advanced Air Electrode Design with Li Metal Anode Protection. Issue 2 (14th December 2018) - Zhao, Changtai; Liang, Jianneng; Sun, Qian; Luo, Jing; Liu, Yulong; Lin, Xiaoting; Zhao, Yang; Yadegari, Hossein; Banis, Mohammad Norouzi; Li, Ruying; Huang, Huan; Zhang, Li; et al.
Abstract: Development of Li‐O2 batteries with ultrahigh theoretical energy density is highly desired to meet the ever‐increasing demand of energy density. However, safety concerns and cycling life have become main bottlenecks that inhibit the practical applications of Li‐O2 batteries because of the use of organic liquid electrolytes (LEs) and the noneffective air electrodes. Gel polymer electrolytes (GPEs) are reported to be used in Li‐O2 batteries and show relatively improved performance than LEs, but they are still below the expectation. Herein, a quasi‐solid‐state Li‐O2 battery constructed with a GPE and a high‐efficiency air electrode is proposed. Excellent electrochemical performance is demonstrated beyond the batteries with LE, evidenced by the ultralong cycle life of up to 553 cycles and stable operating time for over 1100 h. The elongated cycling life benefits from the role of GPE in blocking O2 crossover, protecting Li metal, and avoiding electrolyte evaporation compared with LE. It is expected that the present study can shed light on the future study on developing efficient catalysts for (quasi) solid‐state Li‐O2 battery. Abstract : Quasi‐solid‐state Li‐O2 batteries with an ultralong cycling life of up to 553 cycles are built by pairing an advanced gel polymer electrolyte (GPE) with a high efficiency air electrode. The elongated cycling life benefits from the role of GPE in blocking O2 crossover, protecting Li metal, and suppressing electrolyte evaporation and high catalytic activity of ultrafine RuO2 nanoparticles.